Identification and Characterization of fhuD1 and fhuD2, Two Genes Involved in Iron-Hydroxamate Uptake in Staphylococcus aureus - Sebulsky, M. Tom (American Society for Microbiology, 2001)
Staphylococcus aureus can utilize several hydroxamate siderophores for growth under iron-restricted conditions. Previous findings have shown that S. aureus possesses a cytoplasmic membrane-associated traffic ATPase that is involved in the specific transport of iron(III)-hydroxamate complexes. In this study, we have identified two additional genes, termed fhuD1 and fhuD2, whose products are involved in this transport process in S. aureus. We have shown that fhuD2 codes for a posttranslationally modified lipoprotein that is anchored in the cytoplasmic membrane, while the deduced amino acid sequence predicts the same for fhuD1. The predicted FhuD1 and FhuD2 proteins share 41.0% identity and 56.4% total similarity with each other, 45.9 and 49.1% total similarity with the FhuD homolog in Bacillus subtilis, and 29.3 and 24.6% total similarity with the periplasmic FhuD protein from Escherichia coli. Insertional inactivation and gene replacement of both genes showed that while FhuD2 is involved in the transport of iron(III) in complex with ferrichrome, ferrioxamine B, aerobactin, and coprogen, FhuD1 shows a more limited substrate range, capable of only iron(III)-ferrichrome and iron(III)-ferrioxamine B transport in S. aureus. Nucleotide sequences present upstream of both fhuD1 and fhuD2 predict the presence of consensus Fur binding sequences. In agreement, transcription of both genes was negatively regulated by exogenous iron levels through the activity of the S. aureus Fur protein.